Clinical use of duplicate complete dentures: A narrative review - Nobuhiro Yoda; Masumi Abe; Hirofumi Yamaguchi; Naomi Tanoue; Tetsuo Yamamori (Elsevier, 2024)
Most reports on duplicate dentures are introduction to fabrication methods or clinical case reports. Only a few studies have verified their clinical effectiveness; hence, evidence to construct useful clinical guidelines for duplicate denture use is lacking. This review aimed to comprehensively investigate reports on duplicate dentures to accumulate evidences that will contribute to the formulation of clinical practice guidelines. Duplicate dentures are effectively used for impression making and bite registration when fabricating new dentures, thereby reducing the number of clinic visits and treatment time. Duplicate denture can also be used as temporary or new dentures. Older people in whom various adaptive abilities have declined, may find it difficult to adjust to new dentures and experience stress, even if the shape is appropriate. Duplicate dentures, which reproduces the shape of old dentures that they are used to, have the advantage of being more familiar to older people and less stressful. When manufacturing duplicate dentures, digital methods such as milling and three-dimensional printing are superior to conventional methods regarding working time and cost. A notable advantage of the digital method is that the denture shape can be saved as digital data, and the denture can be easily duplicated if lost.